The Concept of Magic in The Qur’an: An Encyclopedic Semantic Analysis - Fauzani, Naufal Syauqi; Akmaliyah, Akmaliyah (Jurnal Iman dan Spiritualitas, 2025)
This study aims to discuss the concept of magic (sihr) in the Qur’an using an encyclopedic semantic approach. The formal object of this research is the semantic study of the Qur’an, while the material object is the concept of magic in the Qur’an. The context of this study is encyclopedic semantics. The research method is qualitative, employing descriptive-analytical methods and is based on library research. The findings of this study indicate that the word sihr in the Qur’an has a basic meaning of the last part of the night, before the break of dawn, where the darkness of the night meets the light of dawn. This makes anything present during that time appear unclear and indistinct. This meaning is also found in pre-Islamic poetry texts and authoritative Arabic dictionaries. Moreover, the basic meanings found in these dictionaries include meanings reflected in the Qur’an, such as ambiguity, hiddenness, deception, and others. Additionally, the meaning of sihr in the Qur’an has undergone a shift toward a more specific negative connotation. This is evidenced by the frequent association of the term sihr with negative words or meanings in the Qur’an, although the Qur’an still retains its basic meanings from the pre-Islamic period, such as the dawn, something attractive and beautiful, as well as abundance in food and drink.